Schisandrin B improves cerebral ischemia and reduces reperfusion injury in rats through TLR4/NF-κB signaling pathway inhibition. (2nd August 2020) - Fan, Xingjuan; Elkin, Kenneth; Shi, Yunwei; Zhang, Zhihong; Cheng, Yaqin; Gu, Jingxiao; Liang, Jiale; Wang, Caiping; Ji, Xunming
ABSTRACT: It has been established that poor outcomes in ischemic stroke patients are associated with the post-reperfusion inflammatory response and up-regulation of TLR4. Therefore, suppression of the TLR4 signaling pathway constitutes a potential neuroprotective therapeutic strategy. Schisandrin B, a compound extracted from Schisandra chinensis, has been shown to possess anti-inflammatory and neuroprotective properties. However, the mechanism remains unclear. In the present study, the therapeutic effect of schisandrin B was assessed following cerebral ischemia and reperfusion (I/R) injury in a model of middle cerebral artery occlusion and reperfusion (MCAO/R) in rats. The effects of schisandrin B were investigated with particular emphasis on TLR4 signal transduction and on the inflammatory response. Schisandrin B treatment conferred significant protection against MCAO/R injury, as evidenced by decreases in infarct volume, neurological score, and the number of apoptotic neurons and inflammatory signaling molecules. Abbreviations: I/R: schemia/reperfusion; IL: interleukin; MCAO/R: middle cerebral artery occlusion and reperfusion; NF-κB: nuclear; TLR4: Toll-like receptor 4; TNF-α: tumor necrosis factor-α